Annual Statistical Abstract for Tamil Nadu for the Year 1981-82 - Planning Commission (Planning Commission, 1981)
Select Economic Indicators Climate and Rainfall Area and Population, Climate and Rainfall, Rainfall by Districts, Temperature at select stations, Area and Population, Area by Districts, Population by Districts, Density, Sex Ratio, Variation in Population,—Literacy and Rural Urban Ratios, Variation in Population, Scheduled Castes and Scheduled Tribes, Literate Persons
Department of Statistics, Madras